Clinical, Laboratory, and Treatment Profiles of Silent Corticotroph Adenomas That Have Transformed to the Functional Type: A Case Series With a Literature Review - Zheng, Guangyao; Lu, Lin; Zhu, Huijuan; You, Hui; Feng, Ming; Liu, Xiaohai; Dai, Congxin; Yao, Yong; Wang, Renzhi; Zhang, Huabing; Sun, Xu; Lu, Zhaolin (Frontiers in Endocrinology, 2020)
Purpose: Silent corticotroph adenoma (SCA) is clinically nonfunctional pituitary adenoma with expression of corticotropin or Tpit. To further understand the characteristics of this rare type of SCA transforming to a functional SCA, we retrospectively reviewed SCAs that converted to typical Cushing’s syndrome at a tertiary medical center and the relevant literature. Methods: Patients were identified based on the diagnosis of pituitary adenoma without symptoms of hypercortisolism at the initial visit with positive Immunohistochemical (IHC) staining for corticotropin or Tpit after surgery and subsequent transformation to functional SCAs during the follow-up period from March 1990 to January 2020 at Peking Union Medical College Hospital and in the literature. The characteristics of the clinical manifestations, biochemical results, imaging findings, pathology findings and outcome were analyzed. Results: Altogether, 16 patients were included in the study with an average age of 42.0 ±12.48 (18-65) years at the first visit. Females were slightly predominant (F:M=1.3:1). The median time of conversion from the nonfunctional to the functional type was 30 (13.0, 68.3) months. Once a functional SCA developed, the adrenocorticotropic hormone (ACTH) level and 24-h urine free cortisol were increased 3.8- (2.6, 12.9) and 5.3- (2.6, 19.3) fold, respectively, above the normal range. Approximately 50% of the patients had macrocystic changes on pituitary MRI. All 16 patients experienced 1-5 surgeries with a median of 2.5 (2.0, 4.0) surgeries. The proportion of patients with Ki-67≥3% increased from 22.2% (2/9) at the beginning to 50% (7/14) at the time of functional SCA diagnosis. Thirteen patients received radiotherapy, and 4 patients (30.8%) achieved remission. Four patients with refractory functional SCAs received temozolomide treatment with the normalization of cortisol in 4 cases and reduced tumor volume in 3 cases. Conclusion: In this study, all cases that transformed to functional SCAs were macroadenomas. Hypercortisolism was more severe in functional SCA patients. The tumors tended to have frequent recurrence and were highly invasive. Temozolomide could be a promising treatment for refractory functional SCA cases. Long-term follow-up is needed for nonfunctional SCAs since some cases have the potential to transform to clinical Cushing’s syndrome.